A Comparative Analysis of Teacher Education Pathways: United States vs. Vietnam - Linh, Doan Nguyet; L. Bell, Randy (VNU Journal of Science: Education Research, 2024)
This report provides a comparative analysis of teacher education pathways in the United States and Vietnam, focusing on the diversity of options and requirements, advanced educational attainment of novice teachers, and their subject assignments. Both countries offer traditional undergraduate and postgraduate pathways, and the U.S. offers alternative pathways. Traditional programs in the U.S. typically involve a four-year undergraduate degree in education followed by certification, while alternative programs, such as Teach for America, allow prospective teachers to work full-time in classrooms while completing their education coursework. In Vietnam, teacher education often involves specialized training programs within universities that emphasize pedagogy and subject knowledge. Novice teachers in the U.S. frequently pursue advanced degrees within the first few years of teaching. In Vietnam, advanced education is less common among novice teachers, who instead focus on continuous professional development. Subject assignments in the U.S. are typically aligned with teachers' training and certification areas, but teacher shortages can lead to out-of-field teaching. In contrast, subject assignments in Vietnam are more rigid, with teachers usually teaching subjects they specialized in during their training. This report highlights the strengths and challenges of each system and thus contributes to the global discourse on teacher education, aiming to inform policy decisions and improve teacher preparation programs worldwide.